Male circumcision: care practices and attitudes in a Muslim community of western Nepal (Italian Journal of Public Health, 2011)
Background: Male circumcision is a removal of the foreskin of the glans penis. There are medical, ritualand religious reasons for male circumcision. The purpose of this study is to explore the current practices,perceptions, future recommendations and health seeking behavior during and after performing malecircumcision in a Muslim community of western Nepal.Method: A total of 64 households were sampled by a simple random sampling method. Information wascollected using semi-structured questionnaires and focus group discussions.Result: Circumcision was practiced among all Muslim households and the main reason was religious riteand ritual. It was the traditional circumciser, locally known as hazam, who circumcised all male children inthe community. Interestingly, in only 5 % of the household children had been circumcised using modernmedicines. The rest of the households, i.e. 95%, relied on traditional healing systems, the use of local herbsand homemade ointments (mainly the suspension of ghee and ash). A Non-sterilized knife was the mainsurgical instrument used during circumcision. The wound healing after circumcision was much longer, evenup to 90 days or more.Conclusions: Circumcision is a practice that is still largely carried out outside the domain of the formalhealth care system in this community. It demands a design of service delivery models from health policymakers in the Ministry of Health, thus bringing circumcision within formal health care systems in thosecommunities. It deserves an urgent attention to provide safe, culturally acceptable and sustainable servicesfrom health institutions.
Keywords: male circumcision; care practice and attitude; Nepal